Association between metabolic dysfunction-associated steatotic liver disease and risk of incident pancreatic cancer: a systematic review and meta-analysis of cohort studies - Zhang, Yi; Zhou, Ben-Gang; Zhan, Ji-Dong; Du, Bin-Bin (Frontiers in Oncology, 2024)
Background and objectives: Since the results of previous observational studies on the relationship between metabolic dysfunction-associated steatotic liver disease (MASLD) and pancreatic cancer were still controversial and inconsistent, we performed a systematic evaluation and meta-analysis of cohort studies to assess any potential association.We conducted a systematic search of PubMed, Embase, and Web of Science databases from the database's inception up to November 30, 2023. For summary purposes, hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using random-effects models, and subgroup and sensitivity analyses were performed as well. The Egger's test and Begg's test were utilized to detect the publication bias.Results: This meta-analysis included nine cohort studies with a total of 10,428,926 participants. The meta-analysis demonstrated an increased risk of pancreatic cancer in those with MASLD (HR = 1.32, 95% CI: 1.10-1.59, P = 0.003) with moderate heterogeneity (I 2 = 54%, P = 0.03). Subsequent subgroup analyses revealed that the pooled HRs remained significantly unchanged, irrespective of the study area, nomenclature of fatty liver disease, and sample size. The results of the sensitivity analyses remained unchanged. No evidence of publication bias was found.This meta-analysis indicated that MASLD was associated with a higher risk of pancreatic cancer. To further strengthen the association, future prospective cohort studies should take into account different ethnic groups, diagnostic methods of fatty liver, the severity of MASLD, and potential confounding factors, as well as explore the potential mechanisms of pancreatic cancer development in MASLD patients.